Influence of Chewing Cycles on Flavor Recognition Time in Healthy Adults. (July 2019) - Miyaoka, Satomi; Iwamori, Hajime; Miyaoka, Yozo
Flavor recognition times were measured in 23 young, healthy participants of both sexes using an electromyography-based system. The participants were instructed to chew a gummy candy, which was randomly selected among six commercially available types, and to press a button immediately on flavor recognition. A total of 107 normally distributed, flavor recognition times were analyzed, with an average time of 7.5 seconds (± 2.34 seconds, standard deviation). No significant differences were found among the six types of candies in terms of recognition time. Analysis of the association between flavor recognition and chewing phase showed that 70 (65%) of the analyzed 107 recognition signals occurred between 0.2 seconds before and 0.4 seconds after the end of jaw closing. Recognition signals occurring during the jaw-opening phase prolonged its duration by an average of 21%, whereas those occurring during the jaw-closing phase did not influence it.